Bilingualism and Literary (Non-)Translation: The Case of Trieste and Its Hinterland - Ožbot, Martina (Meta, 2014)
This article addresses the question of weak translation activity in bilingual settings. It presents an analysis of the situation in the city of Trieste and its surroundings, where a substantial Slovene minority has lived for centuries alongside the Romance-speaking (mainly Italian) population as well as various other smaller ethnic groups. The Italian and the Slovene communities have had different histories and at various points conflicts between them have arisen, sparked by national issues and complicated further by political circumstances. To a large extent, the two ethnic groups have lived parallel lives, often showing only minimal interest in each other’s culture. This has had an impact on literary translation, the output of which has been rather modest until recently, and often even more so on the reception of translated works – in spite of the city’s rich literature in both Italian and Slovene. This article seeks to identify and explore the nature of this translational relationship, taking into account the underlying social, political, cultural, literary, and linguistic factors. It argues that the situation began to change in the early 1990s when the asymmetries between the two ethnic groups started to diminish and the Slovene culture and language gained greater recognition, which in turn opened new prospects for translation.